Primary urachal leiomyosarcoma: a case report and literature review of clinical, pathological, and medical imaging features - Yan, Jing; Li, Hongwei; Yan, Gaowu; Duan, Qing; Tang, Chunyan; McClure, Morgan A.; Bhetuwal, Anup; Li, Yong; Yang, Ling; Li, Ruyi; Tan, Gangcheng; Feng, Bo (Frontiers in Oncology, 2023)
Background: Urachal tumors are exceedingly rare, and adenocarcinoma is the most common malignant urachal neoplasm. Here, an especially rare patient of primary urachal leiomyosarcoma from our hospital was reported, and only five patients have been reported thus far since 1981.Case Description: A 24-year-old man was admitted due to urinary tract symptoms. Both urogenital ultrasonography and contrast-enhanced computed tomography showed a mass at the dome of the urinary bladder. Laparoscopic surgical resection was performed, and histopathologic examination of the mass confirmed the diagnosis of urachal leiomyosarcoma. No recurrence was noted after one and a half years.Because the leiomyosarcoma located in the extraperitoneal space of Retzius and may manifest with nonspecific abdominal or urinary symptoms, early and definitive preoperative diagnosis is challenging. Partial cystectomy with complete excision of the urachus is recommended.Because only a few patients have been recorded, clinical outcomes and recurrence risks are difficult to assess.